2006
DOI: 10.3758/bf03193436
|View full text |Cite
|
Sign up to set email alerts
|

Strategy shifts in classification skill acquisition: Does memory retrieval dominate rule use?

Abstract: Strategies adopted by participants during skill acquisition do not necessarily remain stable over training or practice trials, but rather often shift in the direction of speeding up responses and easing the cognitive load (Schunn & Reder, 2001). A number of formal models, notably by Logan (1988) and Rickard (1997), have been proposed to account for strategy shifts. These models have focused on a shift from performance based on a rule (algorithm, calculation) to performance based on the retrieval of previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 23 publications
8
36
1
Order By: Relevance
“…For example, Baddeley and colleagues (Baddeley, 1992;Baddeley, Thomson, & Buchanan, 1975), as well as more recent studies (Bourne, Healy, Kole, & Graham, 2006;Hulme, Thomson, Muir, & Lawrence, 1984) found that the faster stimuli were named, the greater the number recalled. The present study extends those findings by identifying a key role played by developing rehearsal skills in this process.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Baddeley and colleagues (Baddeley, 1992;Baddeley, Thomson, & Buchanan, 1975), as well as more recent studies (Bourne, Healy, Kole, & Graham, 2006;Hulme, Thomson, Muir, & Lawrence, 1984) found that the faster stimuli were named, the greater the number recalled. The present study extends those findings by identifying a key role played by developing rehearsal skills in this process.…”
Section: Discussionmentioning
confidence: 94%
“…Following up on that, it might actually be the case that the rule integration strategy is not the most efficient one, given that it is actually slowing the participants down. Moreover, given that rule-based and item-based strategies are not mutually exclusive in the long run (Bourne, Healy, Kole, & Graham, 2006), it can be assumed that with even more task practice, the majority of the participants might shift to an item-based strategy.…”
Section: Incongruent Rule Integration-rule Mismatchmentioning
confidence: 99%
“…More specifically, the objective is to elucidate the neural correlates of quantitative and qualitative strategy differences. Findings from categorization learning literature (Bourne et al, 2006;Bourne et al, 2010) as well as our own behavioral pilot studies (Wolfensteller and von Cramon, unpublished data) suggest that the vast majority of participants begin with a rule-based strategy and only later gradually switch to a more item-based strategy. In line with these findings, it was hypothesized that the RLPFC would be engaged in both subgroups of participants but more so in participants who adhere to the rule-based strategy.…”
Section: Introductionmentioning
confidence: 87%
“…However, behavioral pilot studies (Wolfensteller & von Cramon, unpublished data) and findings from categorization learning (Bourne et al, 2006(Bourne et al, , 2010 suggested that most people initially start out with rule-based strategies. Based on that we hypothesized a gradual transition from rule integration to itembased strategy and hence a quantitative strategy effect at an earlier stage of learning.…”
Section: Rule Integration-a Case For the Rostrolateral Prefrontal Cortexmentioning
confidence: 94%
See 1 more Smart Citation